Reinventing Cooperative Power: Institutional Strengthening of The Koperasi Merah Putih, Parit Baru Village - Rusdiono, Rusdiono; Zhan, Fuzy Firda; Jalius, As'ad Albatroy; Shadrina, Dina Nur (Universitas Muhammadiyah Mataram, 2026)
Abstract: Parit Baru Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan Province, already has a Red and White Cooperative established based on Presidential Instruction of the Republic of Indonesia Number 9 of 2025. However, the institution faces several obstacles including weak governance and institutions within it. Therefore, this community service activity was carried out with the aim of supporting the improvement of insight, knowledge, and procedures for cooperative management in supporting the strengthening of the Red and White Cooperative institution with the principles of good cooperative governance. This activity was carried out in stages, namely with a systematic method: (1) conducting potential mapping, (2) providing counseling regarding the institution and governance of the Red and White Cooperative, and (3) formulating strategies for strengthening the institution and governance through SWOT analysis. The results of this activity are an increased understanding of the management and strengthening of the institution and its governance. In addition, the Collective Participation-Based Strengthening Model is also formulated in four main principles: (1) increasing member capacity through continuing education; (2) transparent, accountable, and participatory cooperative governance; (3) diversification of productive businesses based on local potential; and (4) the use of digital technology and Artificial Intelligence (AI). This model can be used as a basis for developing more systematic and sustainable community empowerment methods for the Merah Putih Cooperative, even on a national scale.Abstrak: Desa Parit Baru, Kecamatan Sungai Raya, Kabupaten Kubu Raya, Provinsi Kalimantan Barat, telah memiliki Koperasi Merah Putih yang didirikan berdasarkan Instruksi Presiden Republik Indonesia Nomor 9 Tahun 2025. Namun, lembaga tersebut mengalami beberapa kendala termasuk masih lemahnya tata kelola dan kelembagaan di dalamnya. Oleh karena itu, kegiatan pengabdian masyarakat ini dilakukan dengan tujuan untuk mendukung peningkatan wawasan, pengetahuan, dan prosedur pengelolaan koperasi dalam mendukung penguatan lembaga Koperasi Merah Putih dengan prinsip tata kelola koperasi yang baik. Kegiatan ini dilakukan secara bertahap yakni dengan metode sistematis: (1) melakukan pemetaan potensi, (2) memberikan konseling mengenai lembaga dan tata kelola Koperasi Merah Putih, dan (3) merumuskan strategi penguatan lembaga dan tata kelola melalui analisis SWOT. Hasil dari kegiatan ini adalah peningkatan pemahaman tentang pengelolaan dan penguatan lembaga serta tata kelolanya. Selain itu, Model Penguatan Berbasis Partisipasi Kolektif juga dirumuskan dalam empat prinsip utama: (1) peningkatan kapasitas anggota melalui pendidikan berkelanjutan; (2) tata kelola koperasi yang transparan, akuntabel, dan partisipatif; (3) diversifikasi usaha produktif berdasarkan potensi lokal; dan (4) pemanfaatan teknologi digital dan Kecerdasan Buatan. Model ini dapat digunakan sebagai dasar untuk mengembangkan metode pemberdayaan masyarakat yang lebih sistematis dan berkelanjutan untuk Koperasi Merah Putih bahkan dalam skala nasional.